(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article provides an understanding of the balance sheet, which is the main document of accounting in banks. The balance sheet is based on the equality of assets and liabilities, its reflection of the financial condition of banks, and its role in the accounting process are analyzed based on local scientific literature. The structure, types, and its importance in the activities of banks are also highlighted